Fenomenologi Sumber Daya Manusia Sebagai Aset Intelektual Dalam Amal Usaha Muhammadiyah - Irman Mamulati; Iwan Triyuwono; Aji Dedi Mulawarman (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
Research is aimed to disclose the meaning of human resource as the intellectual assets. This study used a qualitative paradigm interpretive phenomenological to interpret the human resources as the intelectual assets in Amal Usaha Muhammadiyah. Result of research indicates that the intellectual assets in Amal Usaha Muhammadiyah are signified as the disseminator of knowledge and the driver of dakwah, income source and also expense.